Stalin's ocean-going fleet : Soviet naval strategy and shipbuilding programmes, 1935-1953 /: Soviet naval strategy and shipbuilding programmes, 1935-1953. (2016) - Rohwer, Jürgen; Monakov, Mikhail S
No abstract available